2020
DOI: 10.1186/s41241-020-00085-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry analysis of checkpoint kinase 2 in oral squamous cell carcinoma

Abstract: Background: Oral squamous cell carcinoma (OSCC) is the most frequently occurring malignant tumor of the head and neck region. Chk2 (Checkpoint kinase 2) is considered a tumor suppressor gene that acts on the cellular response to DNA damage. However, the role of Chk2 in OSCC prognosis is not yet fully understood. The objective of this study was to evaluate Chk2 immunoexpression in OSCC and to elucidate the association between its expression and clinicopathological parameters of prognostic importance, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…16,17 However, a recent study indicated there is no significant relation between CHK2 expression and clinicopathological data or survival in oral squamous cell carcinoma. 18 In this research, our data showed that both active form of CHK2 and total CHK2 protein expressions were higher in LSCC tissues than in matched adjacent nontumor tissues. Further, positive expression of CHK2 was closely associated with advanced clinical features and poor prognosis.…”
Section: Introductionmentioning
confidence: 49%
“…16,17 However, a recent study indicated there is no significant relation between CHK2 expression and clinicopathological data or survival in oral squamous cell carcinoma. 18 In this research, our data showed that both active form of CHK2 and total CHK2 protein expressions were higher in LSCC tissues than in matched adjacent nontumor tissues. Further, positive expression of CHK2 was closely associated with advanced clinical features and poor prognosis.…”
Section: Introductionmentioning
confidence: 49%